PEMILU SERENTAK DALAM KAITANNYA TERHADAP REAKSI PASAR MODAL DI INDONESIA - Niken Kusumawardani (Faculty of Economics and Business, 2020)
This study aims to determine the effect of simultaneous elections in Indonesia, namely legislative and executive elections that occur simultaneously together with the reaction in the capital market. Market reaction is measured using trading volume activity and returns stock that occur within the timeframe before and after the holding of simultaneous elections, namely on the date before and after April 17, 2019. The population in this study is the issuer that actively trades its shares on the Indonesia Stock Exchange (IDX) in Compass100 Index stock category. The research hypothesis was tested with an independent sample t-test using software SPPS26. Hypothesis testing results indicate a significant difference in trading volume activity that occurs before and after simultaneous elections. While the variable abnormal return there is no significant difference before and after the election simultaneously. This research is expected to be a reference for all parties concerned including the public towards a political event that occurs in this case specifically the simultaneous elections for decision making related to investment activities in stock instruments